2007
DOI: 10.1039/b617587b
|View full text |Cite
|
Sign up to set email alerts
|

An orthogonal ferromagnetically coupled tetracopper(ii) 2 × 2 homoleptic grid supported by µ-O4bridges and its DFT study

Abstract: A pyrazole based ditopic ligand (PzOAP), prepared by the reaction between 5-methylpyrazole-3-carbohydrazide and methyl ester of imino picolinic acid, reacts with Cu(NO3)2.6H2O to form a self-assembled, ferromagnetically coupled, alkoxide bridged tetranuclear homoleptic Cu(II) square grid-complex [Cu4(PzOAP)4(NO3)2] (NO3)2.4H2O (1) with a central Cu4[micro-O4] core, involving four ligand molecules. In the Cu4[micro-O4] core, out of four copper centers, two copper centers are penta-coordinated and the remaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 30 publications
(14 reference statements)
2
18
0
Order By: Relevance
“…The ligands that formed two chelating rings with copper(I), such as L3, L8-10, were less efficient than L2, which formed one chelating ring with copper(I); this can probably be ascribed to the strong coordinating ability of the former to copper(I), because the catalytically active species involves the simultaneous coordination of both nitrogen and oxygen atoms to the copper(I) atom. [8,23] To determine the most suitable reaction conditions for the N-arylation of imidazole, the catalytic system was examined by using different copper sources, bases, solvents, and catalyst loading; the results are listed in Table 1. It was found that the copper source is important for effective catalysis; CuI was the most reactive, and the respective combination of CuBr, CuSO 4 ·5H 2 O, and Cu with either L2 or Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ligands that formed two chelating rings with copper(I), such as L3, L8-10, were less efficient than L2, which formed one chelating ring with copper(I); this can probably be ascribed to the strong coordinating ability of the former to copper(I), because the catalytically active species involves the simultaneous coordination of both nitrogen and oxygen atoms to the copper(I) atom. [8,23] To determine the most suitable reaction conditions for the N-arylation of imidazole, the catalytic system was examined by using different copper sources, bases, solvents, and catalyst loading; the results are listed in Table 1. It was found that the copper source is important for effective catalysis; CuI was the most reactive, and the respective combination of CuBr, CuSO 4 ·5H 2 O, and Cu with either L2 or Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…The transformation between hindered and functionalized azoles and aryl halides was achieved in good to excellent yields. It is known that acylhydrazine and acylhydrazone derivatives possess high affinity and selectivity to metal ions, [21][22][23] and some insight into their binding and chelating ability to copper has also been explored. [22,23] A broad variety of substituents could also be introduced to the backbone units, which gives an opportunity to flexibly adjust their properties and coordinating ability to metal ions by varying the substituents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16][17][18][19][20] Thus, here we also present a full brokensymmetry density functional theory (BSDFT) investigation to obtain better insight into the exchange coupling of these systems. for 1 and 2, respectively.…”
Section: Introductionmentioning
confidence: 99%